Construções de relações teoria-prática na formação de professores de Ciências e Biologia - Gabriel Menezes Viana (2014)
This study has the objective of understand the construction of theory-practice relationships in Science Teacher Education. In this way, we look through the discursive interactions constructed by prospective science teachers, a teacher-educator and guests in a academic course that aims to teach health education. Furthermore, we dedicated special atention to the relationships between classroom discourses and others discourses constructed in places outside classrom (BLOOME, 2004) The theory-practice relationships (TPR) in teacher education has receive atention by many researches in the field. By one side, there is some studies that discuss dicotomy or associative visions about theory and practice dimensions in those relationships. (i.e.: VÀZQUEZ, 1986; PIMENTA, 1995; CANDAU e LELIS, 1995, 1999) By other side, that are researches that focuses on the TPR in a specific programm of Teacher Education. (e.g.:WAGHORN, STEVENS 1996; HARSTEet al, 2004; SILVA 2009; HONGet al, 2010; DUTRA 2010; HOLLAND, EVANS e HAWKSLEY 2011; MOREIRA, 2012 &PERCY, 2012).Current trends in the field reaffirm the principle of the inseparability of theory-practice relationships in Teacher Education programs. However, are still rare in these investigations a concern to how participants construct theory-practice relationships insideacademic classrooms. Our theoretical and conceptual framework consists of concepts and observations derived from some different fields of study and research. From the field of Teacher Education, we support in the reflections produced by Brazilian and international authors who contributed to the construction of a theoretical framework knowed as the teacher educational models. (SCHÖN, 1983, 1997; 2000; KORTHAGEN, 2001; DINIZ-PEREIRA, 2002, 2007; SANTOS, 2007) The Brazilian Curriculum National Guidelines for teachers education, in special a curricula element knowed as practice as curriculum component (PCC) (BRASIL, 2002a, 2002b) were also important in our research, specifically in help us to identify the curricular spaces to be investigated and also in the pluralization of meanings of practice in teacher education. From the field of Science Education, the contributions of Shulmans works (1986, 1987) of teachers knowledge allow us to characterize the academics disciplines included in the university curriculum. Moreover, we adopted as central in this research the perspective of "t" heory (with lowercase "t"), in other words, as guidelines for the perception of practice of prospective science teachers from the works of Korthagen Kessels (1996); Korthagen and Kessels (1999) and Korthagen (2001). At the same time, the conception of practice adopted in this research was also influenced by perspectives used by others Brazilian scholars as Terreri (2008); Terreri & Ferreira (2013); and Fernandes, Munford & Ferreira (2014). Our methodological and theorical framework was also influenced by some perspectives in the field os Etnography in Education (GREEN, DIXON, ZAHARLIC, 2005; CASTANHEIRA, et al, 2001 e CASTANHEIRA, 2004). These investigations helped us to intepreted classroom as a culture. Furthermore, during the process of research we tried to get close to a few key-principles from that logic of research, like: the study of social practices; the constrative perspective; the holistic persepctive and the iterative-responsive process. The academic discipline investigated was the Laboratory of Teaching Pathology, offered during the second half of the year 2011, in a daytime, in a Science Teacher Education Program, in a large university in southeast Brazil. By making part of a practice as a curriculum component this academic discipline, brings an institutional recognition as a space for the construction of the theory-practice relationships. For data collection we conducted participant observation, interviews with the teacher-educator responsible for the course and collected materials produced for and in the discipline. The data generated in this study were accessed across audio and video records, notebook fielnotes of classroom; audio recordings of interviews with the teachereducator; an inventory of objects in the classroom and artifacts used during the activities in the course. Our analyzes relied on the construction of tables and maps events (DIXON, GREEN, 2005); identifying telling cases (MITCHELL, 1984); characterization of social situations (SPRADLEY, 1980); construction of events (BLOOME et al, 2004); transcription of verbal/oral speech in written word-by-word (CAMERON, 2001) into message units (BLOOME et al, 2004) and analysis of discursive interactions. We selected three moments to analyzes, identified as Events 1, 2 and 3, located in the classes 15, 14 and 8 were selected, respectively. Our results indicate that the theory-practice relationships, when undertaken while the ordering between pedagogical principles and references to the context of professional practice of science teachers, possibly occur at various times, particularly when debates on the activities of teachers in the school are established. In our prespective, these processes generate learning opportunities (BLOOME et al, 2004) around the construction of knowledge about science teaching and, in so, can also be interpreted as moments of building collective reflections. We also identified that, in the events analyzed, participants mobilize lived or imagined experiences, located in different social spaces (linked to school or not). At the same time, across the interactions they mobilize others discourses outside classroom. To investigate this process of discursive construction of the theory-practice relationships in a university classroom allowed us to build reflections that draw attention to the following points: i) the complexity of the processes of theory-practice relationships in the interactions in the classroom; ii) others theories involved in teachers education; iii) the plurality of conceptions of practice in teacher education, and the role of experiences in real schools perfom in the process of theory-practice relationships in Science Teacher Education; and to academics spaces for the construction of theory-practice relationships in Teacher Education and the role of the teacher-educator in that process.